Just mercy [videorecording (DVD)] - Cretton, Destin Daniel; Jordan, Michael B. (Michael Bakari), 1987-; Foxx, Jamie; Morgan, Rob; Nelson, Tim Blake; Larson, Brie, 1989-; Stevenson, Bryan (Warner Bros. Home Entertainment, 2020)
A powerful and thought-provoking true story follows young lawyer Bryan Stevenson and his history-making battle for justice. After graduating from Harvard, Bryan had his pick of lucrative jobs. Instead, he heads to Alabama to defend those wrongly condemned or who were not afforded proper representation, with the support of local advocate Eva Ansley. One of his first and most incendiary cases is that of Walter McMillian.